وظيفة التغاير اللغوي للحركات في اللغة العربية - HUSSEIN, ABBAS ABDELQADER; AHMED, AZZA ADNAN (Journal of Duhok University, 2020)
This study deals with the function of the three movements (Al-Fatha, Al- Kasra, and Al- Dhamma) in bringing about linguistic change in two areas of the Arabic language. The first one is in the heard voices where the movements play an important role in the Arabization of many foreign expressions that are foreign to the language by moving the inhabitant in it with a specific movement or changing a movement with another movement, which leads to the creation of a new language for these words that are completely different from their original language. The second: in the Arabic dialects, where the movements assume the function of a linguistic change between one dialect and another, when two or more words share the same shape, structure and arrangement of letters, their meaning is one in two dialects, the difference between them is only by movements, and this study comes within the framework of the lexical lesson. The research plan included an introduction and an introduction in which it dealt with the concepts of the terms of the study, namely (linguistic variation, Arabization, and local language), then the topic of the study is divided into two sub-topics: The first topic dealt with linguistic frequency in Arabized expressions. The second topic dealt with the linguistic variation in the Arabic dialects in addition to a conclusion that included the most important research results.